Validation of Analytical Method LC MS/MS for Determination Isoniazid in Rats Serum - Suhendi, Andi; Rohman, Abdul; Wahyono, Djoko; Nurrochmad, Arief; Manggo, Tasya Faradillah (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Determination of isoniazid concentration for therapeutic drug monitoring must produce valid values, so validation of the analytical method of LC-MS/MS needs to be carried out. This research aims to obtain valid method of LCMS/MS in order to determination isoniazid in rats serum. Sample preparation was carried out using the liquid-liquid extraction method using acetonitrile and methanol (2:1). The chromatography system was developed with a C18 column (ACQUITY UPLC® HSS T3 1.8 µm, 2.1 × 100 mm), the mobile phase was 70% acetonitrile with 0.1% formic acid (A), water with 0.1% formic acid (B), as well as methanol (C) with a flow rate of 0.3 mL/min, with gradient elution, detection in ESI+ mode with multiple reaction monitoring (MRM) at the transition 138 m/z → 121 m/z. The research results showed that the method was accurate with a % recovery of 96 - 113% and an RSD of 2.4 ± 0.9%. The precision value was obtained with an average RSD of 3.7 ± 2.4% for intra-day and 4.1 ± 2.3% for inter-day. Linearity showed good results with a correlation coefficient of 0.9956 in tests with 5 different concentrations. The LOQ and LOD values obtained from the linear regression equation were 0.1987 µg/mL and 0.0656 µg/mL respectively. The results showed that the LC-M/MS method was valid for determining isoniazid levels in rat serum